The yin and yang of KV channels in cerebral small vessel pathologies. (9th January 2018) - Koide, Masayo; Moshkforoush, Arash; Tsoukias, Nikolaos M.; Hill‐Eubanks, David C.; Wellman, George C.; Nelson, Mark T.; Dabertrand, Fabrice
Abstract: Cerebral SVDs encompass a group of genetic and sporadic pathological processes leading to brain lesions, cognitive decline, and stroke. There is no specific treatment for SVDs, which progress silently for years before becoming clinically symptomatic. Here, we examine parallels in the functional defects of PAs in CADASIL, a monogenic form of SVD, and in response to SAH, a common type of hemorrhagic stroke that also targets the brain microvasculature. Both animal models exhibit dysregulation of the voltage‐gated potassium channel, K V 1, in arteriolar myocytes, an impairment that compromises responses to vasoactive stimuli and impacts CBF autoregulation and local dilatory responses to neuronal activity (NVC). However, the extent to which this channelopathy‐like defect ultimately contributes to these pathologies is unknown. Combining experimental data with computational modeling, we describe the role of K V 1 channels in the regulation of myocyte membrane potential at rest and during the modest increase in extracellular potassium associated with NVC. We conclude that PA resting membrane potential and myogenic tone depend strongly on K V 1.2/1.5 channel density, and that reciprocal changes in K V channel density in CADASIL and SAH produce opposite effects on extracellular potassium‐mediated dilation during NVC.